Association of Gut Microbiota and Metabolites With Disease Progression in Children With Biliary Atresia - Song, Wei; Sun, Li-Ying; Zhu, Zhi-Jun; Wei, Lin; Qu, Wei; Zeng, Zhi-Gui; Liu, Ying; Zhang, Hai-Ming; Guo, Wei (Frontiers in Immunology, 2021)
Background & Aims: Biliary atresia is the most common cause of liver disease and liver transplantation in children. The accumulation of bile acids in hepatocytes and the stimulation of the intestinal microbiome can aggravate the disease progression. This study investigated changes in the composition of the gut microbiota and its metabolites in biliary atresia and the possible effects of these changes on disease progression. Methods: Stool samples of biliary atresia at different disease stages and matched control individuals were collected (early stage: 16 patients, 16 controls; later stage: 16 patients, 10 controls). Metagenomic sequencing was performed to evaluate the gut microbiota structure. Untargeted metabolomics was performed to detect and analyze the metabolites and bile acid composition. Results: A disturbed gut microbiota structure occurred in the early and later stages of biliary atresia. Klebsiella, Streptococcus, Veillonella, and Enterococcus have always been dominant. The abundance of V. atypica displayed significant changes between the early and later stages of biliary atresia. Combined with clinical indicators, Spearman’s analysis showed that Klebsiella and Veillonella atypica strongly correlated with liver enzymes. Enterococcus faecium had an enormously positive relationship with lithocholic acid derivatives. Metabolites involved in tryptophan metabolism were changed in the patients with biliary atresia, which had a significant association with stool V. atypica and blood total bilirubin (P < 0.05). Conclusions: The liver damage of biliary atresia was directly or indirectly exacerbated by the interaction of enriched Klebsiella (K. pneumoniae), Veillonella (V. atypica), and Enterococcus (E. faecium) with dysmetabolism of tryptophan and bile acid.